2015
DOI: 10.1073/pnas.1424638112
|View full text |Cite
|
Sign up to set email alerts
|

N -lactoyl-amino acids are ubiquitous metabolites that originate from CNDP2-mediated reverse proteolysis of lactate and amino acids

Abstract: Despite technological advances in metabolomics, large parts of the human metabolome are still unexplored. In an untargeted metabolomics screen aiming to identify substrates of the orphan transporter ATP-binding cassette subfamily C member 5 (ABCC5), we identified a class of mammalian metabolites, N-lactoyl-amino acids. Using parallel protein fractionation in conjunction with shotgun proteomics on fractions containing N-lactoyl-Phe-forming activity, we unexpectedly found that a protease, cytosolic nonspecific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 56 publications
6
58
0
Order By: Relevance
“…Regardless of their diverse functions, all metabolites were transported into ABCC5-containing vesicles. Vesicular transport of NAAG and ZJ43 shows that ABCC5 has a relatively low affinity for glutamate conjugates, which is comparable to the K m reported for folic acid (1.3 mM) (14) and N-lactoyl-phenylalanine (ϳ1 mM) (16). As the physiological levels of NAAG and BCG can reach millimolar concentrations in the brain, these substrates can still be transported by ABCC5 at considerable rates.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Regardless of their diverse functions, all metabolites were transported into ABCC5-containing vesicles. Vesicular transport of NAAG and ZJ43 shows that ABCC5 has a relatively low affinity for glutamate conjugates, which is comparable to the K m reported for folic acid (1.3 mM) (14) and N-lactoyl-phenylalanine (ϳ1 mM) (16). As the physiological levels of NAAG and BCG can reach millimolar concentrations in the brain, these substrates can still be transported by ABCC5 at considerable rates.…”
Section: Discussionsupporting
confidence: 63%
“…Folate accumulated in Abcc5 Ϫ/Ϫ tissues, but this accumulation was nonsignificant in all tissues except brain. The lack of difference in levels of N-lactoyl-amino acids can be explained by the fact that it is in intracellular equilibrium with the levels of lactate and amino acids (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same transporters have received increasing attention in past years, playing a central role in the absorption, distribution, metabolism and elimination of pharmaceuticals in the human body (Nigam, 2015). In addition, ABC exporters play a major physiological role in the transport of metabolites such as urate, glucuronides and N-lactoyl-amino acids (Jansen et al, 2015; Krumpochova et al, 2012; Woodward et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among these ABC transporters, ABCC5 (also known as MRP5, MOAT-C, pABC11, sMRP) is unique in that, although being related to proteins involved in protective efflux and drug resistance (Belinsky et al, 1998;Chen and Tiwari, 2011;Kool et al, 1997;McAleer et al, 1999), it has not been demonstrated to be toxicologically important (Chen and Tiwari, 2011;Leslie et al, 2001). That ABCC5 effluxes cGMP and cAMP has long been known (Jedlitschky et al, 2000;Sager and Ravna, 2009;Wielinga et al, 2003); however, more recently, heme (Korolnek et al, 2014) and N-lactoyl-amino acids (Jansen et al, 2015) were reported to be possible substrates. Hyaluronan may also be transported by ABCC5 (Schulz et al, 2007), although it is more likely that it is translocated by hyaluronan synthase itself (Medina et al, 2012).…”
Section: Introductionmentioning
confidence: 99%